1989
DOI: 10.1021/bi00435a070
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of collagen gene expression in 3T3-L1 cells. Effects of adipocyte differentiation and tumor necrosis factor .alpha.

Abstract: An early feature in the development of adipocytes from fibroblast-like precursor cells is the biogenesis of an extracellular basement membrane (Napolitano, 1963; Kuri-Harcuch et al., 1984). Interactions between components of the basement membrane (e.g., collagens) and the surfaces of differentiating adipocytes are thought to regulate subsequent phases of the developmental program. Since fibroblasts principally secrete type I and III collagens whereas type IV collagen is abundant in basement membrane, it appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
84
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(96 citation statements)
references
References 39 publications
11
84
1
Order By: Relevance
“…This hormonal agent could act in an autocrine/paracrine manner since it is locally produced by porcine adipocytes in vivo and in vitro [184]. Consistently with its inhibitory effect, its synthesis is decreased during the adipose conversion of 3T3-L1 cells [254]. Finally, TGFβ can also reduce the expression of adipose genes in mature adipocytes [240].…”
Section: Other Growth Factors and Cytokinesmentioning
confidence: 88%
See 1 more Smart Citation
“…This hormonal agent could act in an autocrine/paracrine manner since it is locally produced by porcine adipocytes in vivo and in vitro [184]. Consistently with its inhibitory effect, its synthesis is decreased during the adipose conversion of 3T3-L1 cells [254]. Finally, TGFβ can also reduce the expression of adipose genes in mature adipocytes [240].…”
Section: Other Growth Factors and Cytokinesmentioning
confidence: 88%
“…It can act directly on lipid metabolism by decreasing FA uptake (e.g., decrease in LPL, FAT and FATP expression) and lipogenesis (e.g., decrease in FAS and ACC expression), and by increasing lipolysis [205]. Indirect effects have also been observed since this cytokine can alter collagen (types I, III, and IV) and β-actin synthesis in 3T3-L1 cells [254]. These authors also showed that TNFα could exert its effect by increasing the TGFβ mRNA content.…”
Section: Other Growth Factors and Cytokinesmentioning
confidence: 99%
“…COL1A1 expression is extinguished during adipocyte differentiation and is not expressed in mature adipocytes (27)(28)(29)(30). Therefore, if dominant negative inhibition by p20C/EBP␤ is incomplete in adipocyte progenitors, residual C/EBP activation could promote entry of these cells into the adipogenic program, causing extinction of transgene expression and unimpeded terminal adipocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…*, p Ͻ 0.05; **, p Ͻ 0.001, TNF-␣-treated versus control adipocytes. Exposure to TNF-␣ has been demonstrated to cause a suppression of fat cell gene expression and, in some cases, a dedifferentiation of 3T3-L1 adipocytes (13,37), TA1 adipocytes (3), or human preadipocytes in culture (6). This effect of TNF-␣ on the differentiation process has been related to its inhibitory action on transcription factors that trigger adipogenesis, like C/EBP-␣ (13,14,38,39) or PPAR-␥ (40).…”
Section: Table IV Effect Of Tnf-␣ Treatment On the Lipolytic Activitymentioning
confidence: 99%